The effect of RAFT (Role, Audience, Format, Topic) strategy on writing descriptive texts among eighth-year students at a public school in the city of Loja during 2021-2022 school year Efecto de la estrategia RAFT (Rol, Audiencia, Formato, Tema) en la escritura de textos descriptivos en los estudiantes de octavo año de un colegio público en la ciudad de Loja durante el año lectivo 2021-2022 - Paucar Sisalima, Katty Michelle (2022)
This study was aimed to improve the EFL descriptive writing skills through RAFT (Role, Audience, Topic, Format) strategy among eighth-year students at a public school in the city of Loja during the 2021 - 2022 school year. The research participants were 23 eighth-year students, 13 women and 10 men. In order to carry out this research, a mixed method was used which combines quantitative and qualitative data. For quantitative data, one group pretest-posttest design was applied in order to know the students’ knowledge before and after the treatment. On the other hand, for qualitative data, questionnaires were administered with the purpose of noticing the students’ perceptions regarding to RAFT strategy. The results showed that there was a significant difference (p≤0,05) before and after the treatment which demonstrated that students had a relevant improvement in the descriptive texts aspects such as identification of the phenomena, vocabulary, grammar patterns and mechanics. Additionally, it could be evidenced that RAFT strategy developed their critical thinking skills (imagination, curiosity and research skills) and trigger their interest due to its aspects flexibility (Role, Audience, Format, Topic). Therefore, it was concluded that RAFT strategy improved students’ descriptive texts writing performance as well as activated the students’ imagination, interest and curiosity to develop the RAFT assignments. Key words: Descriptive texts, grammar patterns, identification, mechanics, RAFT strategy, vocabulary.